Sublethal effects of two acaricides, propargite and fenpyroximate on life history of Macrolophus pygmaeus (Hemiptera: Miridae) reared on the two-spotted spider mite eggs - Shima Rahmani; Solmaz Azimi; Parisa Lotfollahi (Persian Journal of Acarology)
Macrolophus pygmaeus (Rambur) is a generalist predator that naturally colonizes and commercially is used as a biological control agent of various arthropod pests of agricultural crops. Since pesticides compatibility with natural enemies is a main concern for IPM programs, the aim of the current study was to assess the lethal and sublethal side effects of two acaricides, propargite and fenpyroximate widely used to control phytophagous mites. In bioassay experiments, M. pygmaeus adult individuals were fed on the two-spotted spider mite eggs immersed in the different concentrations of both chemicals during 24 hours. Probit analysis represented that LC50 values of propargite and fenpyroximate were 3.41 and 5.74 mg (ai) L-1, respectively. Demographic analysis performed with LC30 of each acaricides using the age-stage, two-sex life table procedure. Results showed that both chemicals had significant effects on the developmental time of all stages, the total pre-oviposition period (TPOP), the adult pre-oviposition period (APOP) and females’ fecundity. Also, all main population statistics were affected by the sublethal concentrations. The intrinsic rate of increase (r) was 0.15 day-1 in the control. However, this parameter in propargite and fenpyroximate treatments declined to 0.057 and 0.083 day-1, respectively. The net reproductive rate (R0) in control, propargite and fenpyroximate treated insects was 99.96, 21.16, and 71.5 offspring/individual, respectively. Mean generation time (T) in control showed 30.08 days, whilst it was 53.17, and 51.02 days in propargite and fenpyroximate sublethal treated insects, respectively. Consequently, the results achieved in this study showed that both acaricides have potential to affect the predator, adversely. Thus, they are not suitable for IPM programs in agricultural systems where this mirid bug exists as a capable biocontrol agent.